2015
DOI: 10.1186/s12933-015-0302-4
|View full text |Cite
|
Sign up to set email alerts
|

High visceral fat with low subcutaneous fat accumulation as a determinant of atherosclerosis in patients with type 2 diabetes

Abstract: BackgroundAbdominal visceral obesity has been reported to be associated with cardiovascular risks than body mass index, waist circumference, and abdominal subcutaneous fat. On the other hand, there is evidence that subcutaneous fat has a beneficial role against cardio-metabolic risks such as diabetes or dyslipidemia. However, little is known regarding the association between high visceral fat with low subcutaneous fat accumulation and the risk for atherosclerosis.MethodsThis study was designed to elucidate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 24 publications
2
51
0
5
Order By: Relevance
“…On the other hand, recent studies revealed that not only body weight but also body composition, including body fat mass, is important for cardiovascular risk and mortality . In addition, recent studies revealed a subset of individuals with non‐obese whom the volume of skeletal muscle, and its strength was decreased, so‐called sarcopenia .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent studies revealed that not only body weight but also body composition, including body fat mass, is important for cardiovascular risk and mortality . In addition, recent studies revealed a subset of individuals with non‐obese whom the volume of skeletal muscle, and its strength was decreased, so‐called sarcopenia .…”
Section: Introductionmentioning
confidence: 99%
“…reported in a cross‐sectional study comprising obese participants that the V/S ratio was significantly and positively associated with fasting triglyceride levels and brachial‐ankle pulse wave velocity, a marker of arterial stiffness, but VFA was not associated with brachial‐ankle pulse wave velocity. Additionally, we previously reported that high visceral fat with low subcutaneous fat accumulation is an important determinant of carotid intima‐media thickness, a surrogate marker of atherosclerosis, in patients with type 2 diabetes. However, no data are available on the longitudinal associations of the V/S ratio with incident or recurrent CVD in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that the V/S ratio is a better predictor of the calcium score of the whole aorta, as a marker of atherosclerosis, than SFA or VFA. In addition, we have recently reported in a cross‐sectional study that high VFA with low SFA is an important determinant of carotid atherosclerosis in patients with type 2 diabetes. However, direct evidence is not available as to whether a higher V/S ratio contributes to CVD events in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…La correlación de la razón TAV/TAS y del TAV aislado con el PCC observada en nuestros hallazgos es un resultado que corrobora los resultados presentados por Bouchi y cols. 30 . En esa investigación, realizada con individuos japoneses con DM2, la razón TAV/TAS presentó correlaciones positivas y significativas con aumento del espesor de la capa íntima (ECI).…”
Section: Tav Tav/tasunclassified
“…Recientemente, se reportó que el TAV podría estar asociado a la formación de placa coronaria en pacientes diabéticos, considerándose un factor de riesgo relevante para el desarrollo de aterosclerosis carotídea. Los individuos con alta razón TAV/TAS presentan una menor capacidad para acumular exceso de energía en el depósito subcutáneo, llevando a una acumulación ectópica dentro del músculo, con consecuente aumento del riesgo de aterosclerosis carotídea 30 .…”
Section: Tav Tav/tasunclassified